Strategi Guru Akidah Akhlak dalam Mengatasi Kesulitan Belajar Siswa di Madrasah Tsanawiyah - Anita Sarmila; Afnibar; Ulfatmi (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
Teachers are one of the important components in education that must be responsible for the implementation of the learning process to achieve the desired learning objectives. With the great responsibility of teachers, it is expected that students will not experience difficulties in learning, but if learning difficulties occur, teachers must actively and quickly think of strategies to overcome learning difficulties experienced by students. The role and responsibility of the teacher are expected not to experience difficulties in learning, teachers must create good strategies so that learning difficulties experienced by students can be resolved properly. The purpose of the study was to determine the strategy of akidah akhlak teachers in overcoming learning difficulties of students at the Junior High School. This study uses a qualitative method with a naturalistic approach, namely observing and analyzing research objects as they are, data is collected through literature studies, namely reviewing books, articles and scientific writings related to the theme of the strategy of akidah akhlak teachers in overcoming learning difficulties of students at Junior High Schools. Data is analyzed through data reduction, data display, verification, and conclusions. The results of the study showed that the strategy of the akidah akhlak teacher in overcoming learning difficulties in students was by means of a personal approach and then the teacher provided guidance through extracurricular activities of the rohis and the anisa forum. The factors causing students' learning difficulties in the subject of akidah akhlak are two, namely internal factors which include: lack of interest and motivation of students to learn. And external factors, including: lack of parental guidance especially in terms of reading the Qur'an, minimal family economy, increasingly sophisticated mass media, and also the community environment. The teacher's efforts in overcoming students' learning difficulties in the subject of akidah akhlak are to conduct observations, direct approaches with students, provide guidance through extracurricular activities of the rohis and the anisa forum which are held once a week and the last is to carry out an evaluation.